Considerations about Reducing False-Negative PCR Test for COVID-19 - Alireza Ghannad Sabzevari; Mohsen Nikbakht (Global Health and Education Projects, Inc., 2022)
Polymerase chain reaction (PCR) for the detection of nucleic acids is the gold standard test for the diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, there is the probability of false-negative results with this test, which poses a threat to public health. Here, we highlight some important factors that should be considered for reducing the false-negative results of the SARS-CoV-2 PCR test.   Copyright © 2022 Sabzevari and Nikbakht. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.